Invasive mole presenting as a heavily bleeding vaginal lesion 3 weeks after uterine evacuation. Issue 6 (21st June 2021) - Mamede, Rita; Beja, Mariana; Djokovic, Dusan; Costa, Cristina
Abstract : Gestational trophoblastic disease occurs in 1–3:1000 gestations worldwide. Up to one-fifth of complete hydatidiform moles undergo malignant transformation, with 2%–4% manifesting as metastatic disease. Of these, a third present with vaginal metastases, which can cause bleeding and discharge. We describe the case of a 49-year-old primiparous woman presenting with syncope and intense bleeding from an anterior vaginal lesion, 3 weeks after uterine evacuation for a presumed spontaneous abortion. A vaginal metastatic nodule was suspected; haemostasis was achieved with vaginal packing, precluding the need for surgical intervention. The patient was ultimately diagnosed with invasive mole with vaginal and lung metastases (stage III high-risk gestational trophoblastic neoplasia (GTN)) and started on multiple-agent chemotherapy. Two months later the lesion had regressed completely, and remission was reached 2 weeks later. Clinicians should consider the possibility of metastatic GTN with vaginal involvement whenever heavy vaginal bleeding follows a recent history of failed pregnancy.